2010
DOI: 10.1901/jaba.2010.43-717
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of the Effects of Providing Activity and Material Choice to Children With Autism Spectrum Disorders

Abstract: The present study compares the effects of providing choice between activities or between materials for completion of activities on the on-task behavior of 4 boys with autism spectrum disorders. Results showed that the participants displayed higher levels of on-task behavior during the choice conditions than in the no-choice condition. However, the type of choice opportunity did not seem to have a differential effect.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(14 citation statements)
references
References 11 publications
0
14
0
Order By: Relevance
“…Research has shown that allowing for providing learner customization options plays a critical role in improving self‐regulation of students with disabilities thereby facilitating reading outcomes (Wehmeyer, ). Providing students with disabilities with a choice can improve their academic outcomes and motivation (Tiger, Toussaint, & Roath, ; Ulke‐Kurkcuoglu & Kircaali‐Iftar, ). Furthermore, customization enables students to select the most appropriate level of difficulty and makes CAI adaptable for different levels of students with disabilities (Gerard, Spitulnik, & Linn, ; Jeffs, Behrmann, & Bannan‐Ritland, ; Maich, Hall, van Rhijn, & Henning, ).…”
Section: Discussionmentioning
confidence: 99%
“…Research has shown that allowing for providing learner customization options plays a critical role in improving self‐regulation of students with disabilities thereby facilitating reading outcomes (Wehmeyer, ). Providing students with disabilities with a choice can improve their academic outcomes and motivation (Tiger, Toussaint, & Roath, ; Ulke‐Kurkcuoglu & Kircaali‐Iftar, ). Furthermore, customization enables students to select the most appropriate level of difficulty and makes CAI adaptable for different levels of students with disabilities (Gerard, Spitulnik, & Linn, ; Jeffs, Behrmann, & Bannan‐Ritland, ; Maich, Hall, van Rhijn, & Henning, ).…”
Section: Discussionmentioning
confidence: 99%
“…There is a large body of literature suggesting that structured choice is more appropriate for people with autism than unstructured choice (Tasky et al . ; Ulke‐Kurkcuoglu & Kircaali‐Iftar ; Watanabe & Sturmey ). Therefore, an initial meeting was held in which staff generated a prospective list of topic areas which they felt patients may like to comment on and which linked in with Essence of Care (Department of Health ).…”
Section: Methodsmentioning
confidence: 99%
“…In addition, studies have found that support from classmates and friends contributes to reduced bullying (Gantschnig et al, 2011;Falkmer et al, 2015). Teachers can create opportunities for learning in the way they organise and provide teaching (Hemmingsson & Borell, 2002), including their choice and modifications of assignments and material (Ulke-Kurkcuoglu & Kircaali-Iftar, 2010), computer-assisted instruction in maths and reading (Clarfield & Stoner, 2005;Mautone et al, 2005) and by providing individualised support (Bevan-Brown, 2010;Hellberg, 2007;Sciutto et al, 2012;Tippett, 2004;Tobias, 2009). Cultural matters determine for example both explicit (e.g., raising the hand) and implicit rules (e.g.…”
Section: The Interaction Between the Person And The Environment In Scmentioning
confidence: 99%